Organic Chemistry in Russian Universities. Achievements of Recent Years; Russian Journal of Organic Chemistry; Vol. 60, iss. 8 - Stoikov I. I.; Antipin I. S.; Burilov V. A.; Kurbangalieva A. R.; Rostovsky N. V.; Krasnokutskaya E. A . Elena Aleksandrovna (2024, 2024)
Title screen